Aggregation‐Induced Emission for Highly Selective and Sensitive Fluorescent Biosensing and Cell Imaging. Issue 4 (15th February 2017) - Huang, Liang; Dai, Liming
ABSTRACT: Fluorescent bioprobes are powerful analytical tools for studying biological activities in living systems. Fluorogens with aggregation‐induced emission (AIE) characteristics have recently emerged as a new class of fluorescent bioprobes for biosensing and cell imaging. As discovered by Tang, AIE fluorogens are nearly nonemissive in molecular states with their intermolecular rotations being not restricted whereas their fluorescence is turned on by binding with certain biomolecules, leading to highly selective turn‐on fluorescent probes for specific biomolecules and fluorescent cell imaging with a high signal‐to‐background noise ratio. By introducing the AIE characteristics into polymeric materials, AIE polymers could possess a good solubility and biocompatibility, excellent structural diversity, and ease for functionalization useful for efficient biosensing and cell imaging. Herein, we highlight a few recently published articles on small and macromolecular AIE molecules to provide a fundamental understanding of the AIE mechanism and illustrate the working principle for AIE based biosensing and cell imaging. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 653–659 Abstract : Aggregation‐induced emission (AIE) fluorogens show weak or no fluorescence as molecular species, but intense fluorescence as aggregates. They are promising fluorescent turn‐on probes for highly selective biomolecule detection and cell imaging with a high signal‐to‐background ratio and an excellent photostability.